A case for multimedia streaming over the grid infrastructure - Georgatos, Fotis; Lambrinos, Lambros (My University, 2008)
The grid infrastructure consists of nodes all over the world which are usually interconnected with high speed network links and provide storage and processing facilities. In this paper, we investigate how this massive infrastructure can be utilized to facilitate efficient and scaleable real-time multimedia streaming. The aim is to avoid the issues usually associated with one-to-many media streaming architectures through the use of a mechanism that initiates reflectors as and when they are needed thereby reducing bandwidth-related bottlenecks and ensuring that the delay between the last media distribution point and the receiving client is as low as possible.
Keywords: Architecture; Multimedia systems; Multimedia; Processing facilities; Scaleable; Multimedia streaming